1999
DOI: 10.1289/ehp.99107805
|View full text |Cite
|
Sign up to set email alerts
|

p53 induction as a genotoxic test for twenty-five chemicals undergoing in vivo carcinogenicity testing.

Abstract: In vivo carcinogenicity testing is an expensive and time-consuming process, and as a result, only a relatively small fraction of new and existing chemicals has been tested in this manner. Therefore, the development and validation of alternative approaches is desirable. We previously developed a mammalian in vitro assay for genotoxicity based on the ability of cells to increase their level of the tumor-suppressor protein p53 in response to DNA damage. Cultured (11,16,17) or by initiating a cell's apoptotic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…We subsequently found that silver and cobalt ions severely affect the IC 50 of both cells. Regarding cobalt, Duerksen-Hughes et al (1999) evaluated cobalt sulfate based on the ability of cells to increase the level of the tumor suppressor protein p53 that is activated in response to DNA damage, and found that it had a medium genotoxicity. Also, Lison et al (2001) reported that the cobalt (III) positive ion exhibited genotoxicity and carcinogenesis, but added that the data collected was insufficient to prove this.…”
Section: Discussionmentioning
confidence: 99%
“…We subsequently found that silver and cobalt ions severely affect the IC 50 of both cells. Regarding cobalt, Duerksen-Hughes et al (1999) evaluated cobalt sulfate based on the ability of cells to increase the level of the tumor suppressor protein p53 that is activated in response to DNA damage, and found that it had a medium genotoxicity. Also, Lison et al (2001) reported that the cobalt (III) positive ion exhibited genotoxicity and carcinogenesis, but added that the data collected was insufficient to prove this.…”
Section: Discussionmentioning
confidence: 99%
“…In a recently developed assay for DNA damage measuring induction of p53 tumour suppressor protein in mouse fibroblasts (NTCT 929 cell line) in vitro, citral gave positive results at concentrations of 10-EFSA Journal 2010; 8(11): 1207 30 µg/ml after 17 h of incubation. In this assay, increased expression of p53 is considered to indicate the induction of DNA damage (Duerksen-Hughes et al, 1999).…”
Section: Genotoxicity Studies -Text Taken 4 From the Jecfa (Jecfa 20mentioning
confidence: 99%
“…In a recently developed assay for DNA damage measuring induction of p53 tumour suppressor protein in mouse fibroblasts (NTCT 929 cell line) in vitro, citral gave positive results at concentrations of 10-30 µg/ml after 17 h of incubation. In this assay, increased expression of p53 is considered to indicate the induction of DNA damage (Duerksen-Hughes et al,1999).…”
Section: Genotoxicity Studies -Text Taken 5 From the Jecfa (Jecfa 20mentioning
confidence: 99%
“…Citral was not mutagenic in several valid Ames tests (Gomes-Carneiro et al, 1998;Ishidate et al, 1984;NTP, 2003e;Zeiger et al, 1987), and it did not induce chromosome aberrations in a valid in vitro study with chinese hamster ovary (CHO) cells (NTP, 2003e (Yoo, 1986) and the induction of the tumour suppressor protein p53 (Duerksen-Hughes et al, 1999) are considered of limited relevance for the overall evaluation. The Panel concluded that for citral genotoxicity is not of concern.…”
Section: Genotoxicity Studies and Conclusion Onmentioning
confidence: 99%